Distribution Prediction of Shale Deformation Structures in Tectonically Complex Area Based on Relationship Between Geological Structures and Shale Deformation - Cheng, Guoxi; Jiang, Bo; Li, Fengli; Li, Ming; Song, Yu (Frontiers in Earth Science, 2022)
Taking the Wufeng–Longmaxi shale of the southern Sichuan Basin as the research object, deformation observations of shale outcrops and cores were conducted to reveal the distribution patterns of shale deformation structures in fault and fold structures. On this basis, the distribution rules of shale deformation structures in the unexposed areas were predicted by considering the structural framework of the study area. Our research found that faults can only result in structural deformation of shale in a limited area and that the influences of reverse faults were relatively more significant. Shale near the fault planes of reverse faults usually showed intense folding deformations, with bedding-parallel and crumpled cleavages well developed, and strong deformation structures (crumpled -, mylonitized -, scaly -, fractured-crumpled -, flaky structure) were distributed. Near the fault planes of normal faults, shale deformations were mainly characterized by the increase of tectonic fractures, and shale usually showed cataclastic structure. In the areas affected by strike-slip faults, bedding-perpendicular fractures and the fractures high-angle oblique to bedding planes were well developed, and shale mainly showed cataclastic structure. Compared with faults, folds can cause shale deform in a larger area, and shale deformations showed significant differences in different locations of the same fold. Shale in core zones usually displayed strong deformation structures. In the core–limb transitional areas of folds, there mainly developed bedding-parallel and bedding-perpendicular fractures, and shale usually showed as platy - and cataclastic shale. In the limbs of folds, shale deformations were generally weak, and shale usually showed primary structure and weak brittle deformation structures. Considering the structural framework of the study area, we predicted that strong deformation structures should be mainly distributed in the core zones of anticlines (especially the tight and closed ones) and near the fault planes of large-scale reverse faults, while medium-intensity brittle deformation structures (platy - and cataclastic structure) is distributed in core–limb transitional areas of anticlines and near the normal faults and strike-slip faults. In the limbs of anticlines and the areas controlled by synclines (mostly wide and gentle), shale should mainly show primary structure and weak brittle deformation structures.